Ecological analysis of plant community structure and soil effects in subtropical forest ecosystem - Sehrish Sadia; Muhammad Waheed; Shazia Firdous; Fahim Arshad; Beatrice Ambo Fonge; Abeer Al-Andal (BMC Plant Biology)
Abstract Background Subtropical forest plant diversity, characterized by a wide range of species adapted to seasonal variations, is vital for sustaining ecological balance, supporting diverse wildlife, and providing critical ecosystem services such as carbon sequestration and soil stabilization. The Changa Manga Forest, an ecologically rich area with varied vegetation, was analyzed to understand the intricate relationship between plant diversity and environmental factors. This study investigates the diversity patterns, vegetation structure, and environmental influences on forest biodiversity. Methods A comprehensive survey was conducted across 127 stands within the Changa Manga Forest to document plant species and classify vegetation communities. Soil samples were collected and analyzed for key physicochemical parameters, while multivariate statistical methods, including hierarchical clustering and ordination, were applied to examine the relationships between vegetation structure and environmental factors. Diversity indices and beta diversity components were calculated to assess variations across plant communities. Results The species were classified into six distinct vegetation communities: Neltuma-Ziziphus-Malvestrum (NZM), Broussonetia-Lantana-Morus (BLM), Dalbergia-Lantana-Solanum (DLS), Morus-Abutilon-Ricinus (MAR), Eucalyptus-Vachellia-Sorghum (EVS), and Bombax-Leucaena-Croton (BLC). Analyses using hierarchical clustering and ordination methods revealed significant differences in species composition among these communities, with NZM and DLS exhibiting the highest dissimilarity. Canonical Correspondence Analysis (CCA) indicated that environmental factors such as soil pH, available phosphorus (AP), and organic matter percentage (OM%) are crucial in shaping plant distribution, though the total explained variation remained relatively low. Diversity indices varied significantly among communities, with the NZM community showing the highest Shannon and Simpson diversity, while EVS exhibited the lowest. The beta diversity analysis revealed a high species turnover between certain communities, indicating complex ecological interactions. Our results indicate significant variability in plant community composition and diversity patterns, influenced by edaphic factors and environmental gradients. We anticipate that future environmental changes, such as shifts in soil properties, precipitation patterns, and increased human activity, may exacerbate declines in local plant species richness and disrupt community structures. To preserve the invaluable biodiversity of the study area for future generations, it is essential to implement timely and effective conservation and management strategies.